Impact of Coronary Artery Disease Severity Assessed With the SYNTAX Score on Outcomes Following Transcatheter Aortic Valve Replacement. Issue 2 (February 2017) - Paradis, Jean‐Michel; White, Jonathon M.; Généreux, Philippe; Urena, Marina; Doshi, Darshan; Nazif, Tamim; Hahn, Rebecca; George, Isaac; Khalique, Omar; Harjai, Kishore; Lasalle, Laura; Labbé, Benoit M.; et al.
Abstract : Background: The influence of coronary artery disease (CAD) on clinical and echocardiographic outcomes after transcatheter aortic valve replacement (TAVR) is still controversial. We sought to evaluate the impact of CAD severity as measured by the SYNTAX score (SS) on patients undergoing TAVR. Methods and Results: A total of 377 patients who underwent TAVR in 2 high‐volume centers in North America were included in our retrospective analysis. A blinded angiographic core laboratory calculated the SS on all available coronary angiograms with the use of quantitative coronary analysis. Patients were stratified into 4 groups: (1) no CAD (SS=0); (2) low SS (SS between 1 and 22); (3) intermediate SS (SS between 23 and 32); and (4) high SS (SS ≥33). Patients who had undergone percutaneous coronary intervention within 6 months prior to TAVR were separated into 2 categories based on their residual SS (<8 and ≥8). Patients with previous coronary artery bypass grafting (CABG) were divided into 2 groups: (1) low CABG SS and (2) high CABG SS. The primary end point was a composite of all‐cause mortality, myocardial infarction, and stroke. At 30 days and 1 year, both the presence and the severity of CAD had no impact on the rate of the combined primary end point and on all‐cause mortality, cardiovascular mortality, and myocardial infarction. Patients with less complete revascularization (residual SS ≥8 versus residual SS <8 and low CABG SS versus high CABG SS, had similar rates of the combined primary end point, all‐cause mortality, cardiovascular mortality, MI, and stroke, at both 30 days and 1 year. Conclusions: In our core laboratory–validated study, neither the severity of CAD nor completeness of revascularization after percutaneous coronary intervention or CABG were associated with clinical outcomes after TAVR, at both 30 days and 1 year.